Not just for romance: - Maidment, Jane; Crisp, Beth R. (Groupwork, 2012)
In this article we address how a contemporary adaptation of the ‘speed dating’ model was used for educational purposes with two cohorts of social work students. We outline the dimensions of ‘speed dating’ as a contemporary social phenomenon, then address how this model relates specifically to groupwork process, and can be used to facilitate social work student learning. The curriculum for two classroom group activities using the ‘speed dating’ model are outlined, the first to develop university level study skills, the second for debriefing field placement learning experiences. Finally we examine why the ‘speed dating’ metaphor was successful in provoking a playful yet constructively creative space for students to engage in groupwork process.